The Effect of Extrinsic Motivation on Housewife Actions in IVA Test in the Working Area of Community Health Center at Bandar Kalipah - Vani Olin Arysha; Heru Santosa; Sri Rahayu Sanusi (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Cervical cancer is a cancer that attacks many women. The high number of cervical cancer sufferers in Indonesia is caused by only 5% who screen for cervical cancer, because this disease does not cause symptoms and low awareness of women to check their health. Every woman of childbearing age should be motivated to do an IVA Test. The purpose of this study is to analyze the effect of extrinsic motivation on housewives actions in IVA Test. The design of this study is a case control with 36 samples in cases and controls. Processing data using chi square analysis with a 95% significance level by calculating the odds ratio. The results showed that there was an influence of extrinsic motivation (p = 0,000) on the housewives actions in IVA Test. The results of the analysis showed that the OR 10.969 95% CI (3.425-35.129) that did Possible IVA Test 10.9 is more effect than housewives who have extrinsic motivation.